Estimating a normal reference range for serum B‐cell maturation antigen levels for multiple myeloma patients. (22nd April 2020) - Jew, Scott; Bujarski, Sean; Soof, Camilia; Chen, Haiming; Safaie, Tahmineh; Li, Mingjie; Sanchez, Eric; Wang, Cathy; Emamy‐Sadr, Marsiye; Swift, Regina; Rahbari, Ashkon; Patil, Saurabh; et al.
Summary: The serum B‐cell maturation antigen (sBCMA) has been identified as a novel serum biomarker for patients with multiple myeloma. However, no study has yet established a reference range for sBCMA levels. Its levels were determined in 196 healthy subjects and showed a right‐tailed distribution with a median value of 37·51 ng/ml with a standard deviation of 22·54 ng/ml (range 18·78–180·39 ng/ml). Partitioning of subgroup reference ranges was considered but determined to be irrelevant. A non‐parametric method using the median ± 2 standard deviations suggests using a universal reference interval of <82·59 ng/ml.